Effects of soft robotic exoskeleton for gait training on clinical and biomechanical gait outcomes in patients with sub-acute stroke: a randomized controlled pilot study - Xie, Ruimou; Zhang, Yanlin; Jin, Hainan; Yang, Fei; Feng, Yutong; Pan, Yu (Frontiers in Neurology, 2023)
Background Ankle function impairment is a critical factor impairing normal walking in survivors of stroke. The soft robotic exoskeleton (SRE) is a novel, portable, lightweight assistive device with promising therapeutic potential for gait recovery during post-stroke rehabilitation. However, whether long-term SRE-assisted walking training influences walking function and gait quality in patients following subacute stroke is unknown. Therefore, the primary objective of this study was to assess the therapeutic effects of SRE-assisted walking training on clinical and biomechanical gait outcomes in the rehabilitation of patients with subacute stroke. Methods A group patients who had experienced subacute stroke received conventional rehabilitation (CR) training combined with 10-session SRE-assisted overground walking training (30 min per session, 5 sessions/week, 2 weeks) (SRE group, n = 15) compared with the control group that received CR training only (CR group, n = 15). Clinical assessments and biomechanical gait quality measures were performed pre-and post-10-session intervention, with the 10-Minute Walk Test (10MWT) and 6-Minute Walk Test (6MWT) used to define the primary clinical outcome measures and the Functional Ambulation Category, Fugl-Meyer Assessment for Lower Extremity (FMA-LE) subscale, and Berg Balance Scale defined the secondary outcome measures. The gait quality outcome measures included spatiotemporal and symmetrical parameters during walking. Results After the 10-session intervention, the SRE and CR groups exhibited significant within-group improvements in all clinical outcome measures (p < 0.05). Between-comparison using covariance analyses demonstrated that the SRE group showed greater improvement in walking speed during the 10MWT (p < 0.01), distance walked during the 6MWT (p < 0.05), and FMA-LE scores (p < 0.05). Gait analyses showed that the SRE group exhibited significantly improved spatiotemporal symmetry (p < 0.001) after 10-session training, with no significant changes observed in the CR group. Conclusion Compared with CR training, SRE-assisted walking training led to greater improvements in walking speed, endurance, and motor recovery. Our findings provide preliminary evidence that SRE may be considered for inclusion in intensive gait training clinical rehabilitation programs to further improve walking function in patients who have experienced stroke.